Immunoadsorption therapy for a meningococcemia patient with myocarditis, adrenal hemorrhage, and purpura fulminans: a case report - Nihal Akcay; Hasan Serdar Kihtir; Guner Ozcelik; Ulkem Kocoglu Barlas; Mey Talip Petmezci; Esra Sevketoglu (Brazilian Journal of Anesthesiology, 2022)
Neisseria meningitidis, also known as meningococcus, is a relatively uncommon cause of invasive infection, but when it occurs, it is frequently severe and potentially life-threatening. A ten-year-old female patient developed a purpuric rash with fever. Upon arrival to the pediatric intensive care department, she was unconscious and in a poor general condition. We combined treatment with antibiotics, volume resuscitation, hydrocortisone, and CytoSorb.½ therapy resulted in a stabilization of hemodynamics, as well as control of hyperinflammation. We observed a significant decrease in vasopressor dosage in this patient.